Similarity: outline of a systems theory of community - Vitor Barros (Theory and Society, 2026)
Community studies face a persistent dilemma: weak definitions of community avoid groupism but sacrifice analytical precision, while strong definitions maintain precision through problematic assumptions of social closure, value cohesion and collective agency (i.e., groupism). This article resolves this tension with a theory of communities as social systems, which reproduce as they create and organize a communication mode that establishes a principle of social identity based on a shared similarity. The formation of communities is then explained by the co-occurrence of three processes: distinction, generalization, and structuration. By shifting the focus from questions of belonging (“who is in or out?”) to questions of symbolic boundary-making (“what distinguishes a community?”), the approach rehabilitates the concept without presupposing high solidarity, or social closure. The theory then positions communities in the meso level of society, above interactions, besides social movements and organizations, and below institutional/functional systems. It also demonstrates the analytical difference and empirical usefulness of “community” if compared to the concepts of network, group, and category. The discussion provides, in sum, a framework to observe how communities maintain symbolic distinctiveness while accommodating graduated participation, varying solidarity, and fluid social boundaries within a complex society.
Keywords: 300; Community; Systems theory; Social theory; Similarity; Communication